Information Science and Applications - Kim, Kuinam J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This proceedings volume provides a snapshot of the latest issues encountered in technical convergence and convergences of security technology.  It explores how information science is core to most current research, industrial and commercial activities and consists of contributions covering topics including Ubiquitous Computing, Networks and Information Systems, Multimedia and Visualization, Middleware and Operating Systems, Security and Privacy, Data Mining and Artificial Intelligence, Software Engineering, and Web Technology.   The proceedings introduce the most recent information technology and ideas, applications and problems related to technology convergence, illustrated through case studies, and reviews converging existing security techniques.  Through this volume, readers will gain an understanding of the current state-of-the-art in information strategies and technologies of convergence security. The intended readership are researchers in academia, industry, and other research institutes focusing on information science and technology. .
Part 1 -- QoS-aware Mapping and Scheduling for Integrated CWDM-PON and WiMAX Network; S.H.Mohammad, et al -- Resource Management Scheme Based on Position and Direction for Handoff Control in Micro/Pico -Cellular Networks; D.C.Lee, et al -- A Pilot Study of Embedding Android Apps with Arduino for Monitoring Rehabilitation Process; S.Salim, et al -- A Security Protocol based-on Mutual Authentication Application toward Wireless Sensor Network; B.NDIBANJE, et al -- A Noninvasive Sensor System for Discriminating Mobility Pattern on a Bed; S.H.Cho, S.Cho -- A Fault-Tolerant Multi-Path Multi-Channel Routing Protocol for Cognitive Radio Ad Hoc Networks; Z.Che-aron, et al -- Study of Sound and Haptic Feedback in Smart Wearable Devices to Improve Driving Performance of Elders; C.Natpratan, N.Cooharojananone -- Indoor WIFI localization on embedded systems; A.Apavatjrut, E.Boonyasiwapong -- Bacterial Foraging-based Power Allocation for Cooperative Wireless Sensor Networks; M.Abdul Azim, et al -- Part 2 -- Maintaining a trajectory data warehouse under schema changes with the mobile agent view adaptation technique; W.Oueslati, J.Akaichi -- Traffic Analysis in Concurrent Multi-Channel Viewing on P2PTV; K.Mizutani, et al -- Evaluation Method of MANET over Next Generation Optical Wireless Access Network; M.A.Wong, et al -- A Feedback Mechanism Based on Randomly Suppressed Timer for ForCES Protocol; L.Cen, et al -- Operational Analysis of Arrival Rate-based Queuing Management Mechanism for High-speed Networks; M.M.Kadhum, S.Manickam -- E-Government project enquiry framework for a continuous improvement process, A case study in Malaysia and Comoros; S.A.Mfoihaya, M.Mohd Yusof -- Objective Non-intrusive Conversational VoIP Quality Prediction using Data mining methods; S.Valaisathien, V.Vanijja -- A Hybrid Incentive-based Peer Selection Scheme for Unstructured Peer-to-peer Media Streaming Systems; V.II Romero, C.A.Festin -- A transmission method to improve quality of multimedia in Hybrid Broadcast/ Mobile Networks; H.-Y.Seo, et al -- A Failureless Pipelined Aho-Corasick Algorithm for FPGA-based Parallel String Matching Engine; H.Kim -- Revised P2P Data Sharing Scheme over Distributed Cloud Networks; W.Lee, et al -- LQDV Routing Protocol Implementation Design in Arduino Platform and Xbee module; S.K.HO, M.Kyun Kim -- A Virtualization and Management Architecture of Micro-Datacenter; B.Park, et al -- Multi-disjoint Routes Mechanism for Source Routing in Mobile Ad-hoc Networks; B.Hamza Khudayer, et al -- Passive Network Monitoring using REAMS;  A.Azodi, et al -- Low Latency Video Transmission Device; C.Park, H.Kim -- Part 3 -- Comparative Investigation of Biomedical Contents using Desktop and Tabletop Technologies; T.M.Madni Ikram, et al -- Dynamic-Time-Warping Analysis of Feature-Vector Reliability for Cognitive Stimulation Therapy Assessment; T.Pham -- An Algorithm for Rock Pore Image Segmentation; Z.Jiqun, et al -- Action Recognition by Extracting Pyramidal Motion Features from Skeleton Sequences; G.LU, et al -- P-PCC: Parallel Pearson Correlation Condition for Robust Cosmetic Makeup Face Recognitions; K.Rujirakul, Chakchai So-In -- Flight Simulator for Serious Gaming; A.Nisansala, et al -- Potential Z-Fighting Conflict Detection System in 3D Level Design Tools; P.Setthawong -- Efficient Motion Vector Algorithms for Faster Implementation of HEVC/H.265 Video Coding; E.Jaja, et al -- A Synthesis of 2D Mammographic Image Using Super-Resolution Technique: A Phantom Study; S.Kantharak, et al -- Using complex events to represent domain concepts in graphs; R.Tipton Perry, et al -- Unequal Loss Protection Mechanism for Wi-Fi based Broadcasting system using a Video Quality Prediction Model; D.H.Kim, et al -- An Approximate Matching Preprocessing for Efficient Phase-Only Correlation-Based Image Retrieval; H.Wang, M.Aritsugi -- Pixel Art Color Palette Synthesis; Mi.-R.Huang, R.-R.Lee -- Introducing a New Radiation Detecting Device Calibration Method and Estimating 3D Distance to Radiation Sources; P.Rathnayaka, et al -- Integrating Feature Descriptors to Scanpath-based Decoding of Deformed Barcode Images; P.Yospanya, Y. Limpiyakorn -- Detecting and extracting text in video via sparse representation based classification method; B.Sun, et al -- Part 4 -- A Cost Model for Client-Side CaaS; C.Sriwiroj, T.Banditwattanawong -- A Reliability Analysis of Cascaded TMR Systems; H.J.Yi, et al -- Availability Analysis for A Data Center Cooling System with (n,k)-way CRACs; S.Koo, et al -- A Recovery Model for Improving Reliability of PCM WL-Reviver System; T.Roh, et al -- Real-time Sitting Posture Monitoring System for Functional Scoliosis Patients; J.-Y.Jung, et al -- Part 5 -- Decreasing Size of Parameter for Computing Greatest Common Divisor to Speed up New Factorization Algorithm Based on Pollard Rho; K.Somsuk -- Network Security Situation Assessment: A Review and Discussion; Y.B.Leau, S.Manickam -- Protecting Binary Files from Stack-Based Buffer Overflow; S.Alouneh, et al -- Meet-in-the-middle Attack with Splice-and-Cut Technique on the 19-round Variant of Block Cipher HIGHT; Y.Igarashi, et al -- Nonintrusive SSL/TLS Proxy with JSON-Based Policy; S.Mohd Jawi, et al -- Secure Problem Solving Scheme by Encrypted Computing; H.Yamaguchi, et al -- Anomaly Detection from Log Files Using Data Mining Techniques; J.Breier, J.Branisova -- Improved Remote User Trust Evaluation Scheme to apply to Social Network Services; Y.Kim, et al -- Threat assessment model for mobile malware; T.van Do, et al -- Performance Evaluation of System Resources Utilization with Sandboxing Applications; T.Helmy, et al -- Fault Attacks by using Voltage and Temperature Variations: An Investigation and Analysis of Experimental Environment; Y.Sil Lee, et al -- Pseudoinverse Matrix over Finite Field and Its Applications; V.Dang, T.Nguyen -- Multi-Agent based Framework for Time-correlated Alert Detection of Volume Attacks; A.Olabelurin, et al -- Side Channel Attacks on Cryptographic Module: EM and PA Attacks Accuracy Analysis; H.H.Kim, et al -- Exploring Bad Behaviors from Email Logs; S.Kanchanapokin, S.Boonkrong -- Using PKI to Provide Credential Delegation in non-Web-based Federations; D.Kouril, et al -- Modeling and Simulation of Identification Protocol for Wireless Medical Devices in Healthcare System Communication; H.H.Kim, et al -- A Method for Web Security Context Patterns Development from User Interface Guidelines based on Structural and Textual Analysis; P.Singpant, N.Prompoon -- A Comparative Study of Combination with Different LSB Techniques in MP3 Steganography; M.Salem Atoum -- Review of Digital Investigation Frameworks; R.Agarwal, S.Kothari -- Part 6 -- Knowledge Discovery in Dynamic Data Using Neural Networks; E.Volna, et al -- Data Mining for Industrial System Identification: A Turning Process; K.Kandananond -- Investigating the Effectiveness of E-mail Spam Image Data for Phone Spam Image Detection using Scale Invariant Feature Transform Image Descriptor; S.Y.Kim, K.-A.Sohn -- Features extraction for classification of focal and non-focal EEG signals; K.Rai, et al -- Relations on Intuitionistic Fuzzy Soft Multi Sets; A.Mukherjee, A.Das -- Towards Automatically Retrieving Discoveries and Generating Ontologies; K.Cosh -- Improving process models discovery using AXOR Clustering Algorithm; H.Ariouat, et al -- Simple approaches of sentiment analysis via ensemble learning; T.Chalothorn, J.Ellman -- Effective Trajectory Similarity Measure for Moving Objects in Real-world Scene; M.Ra, et al -- A Prediction of Engineering Students Performance from Core Engineering Course using Classification; N.Rachburee, et al -- Evolutionary Circular-ELM for the reduced-reference assessment of perceived image quality; S.Atsawaraungsuk, P.Horata -- Enhanced Web page Cleaning for Constructing Social Media Text Corpora; M.Neunerdt, et al -- Finding Knee Solutions in Multi-objective Optimization using Extended Angle Dominance Approach; S.Sudeng, N.Wattanapongsakorn -- Affective Learning Analysis of Children in a Card Sorting Game; M.Othman, et al -- Application of Mean and Median Frequency Methods for Identification of Human Joint Angles Using EMG Signal; S.Thongpanja, et al -- A study of Big Data solution using Hadoop to process Connected vehicle's Diagnostics data; L.Nkenyereye, J.-W.Jang -- Wiki SaGa: an Interactive Timeline to Visualize Historical Documents; D.Tan, et al -- Discovering genomic associations on cancer datasets by applying sparse regression methods; R.R.Vangimalla, K.A.Sohn -- The Adaptive Dynamic Clustering of Neuro-Fuzzy System for Classification; P.Napook, N.Eiamkanitchat -- A Hybrid Approach of Neural Network and Level-2 Fuzzy set; J.Teyakome, N.Eiamkanitchat -- Developing Term Weighting Scheme based on  Term Occurrence Ratio for Sentiment Analysis; N.Chirawichitchai -- A Comparison of Artificial Neural Network and Regression Model for Predicting the Rice Production in Lower Northern Thailand; A.Na-udom, J.Rungrattanaubol -- Study on Local Path Planning for Collision Avoidance in Vehicle-to-Vehicle Communication Environment; G.-e.Kim, B.-w.Kim -- Vehicle Position Estimation using Tire Model; J.-w.Yoon, B.-w.Kim -- I know when you are happy - Emotion Detection; A.Singh Kilak, N.Mittal -- Interconnection Learning between Economic Indicators in Indonesia Optimized by Genetic Algorithm; S.Saadah, G.Septiana Wulandari -- Classification Prediction of the Foot Disease Pattern Using Decision Tree Model; J.-K.Choi, et al -- Non-Preference Based Pruning Algorithm for Multi-Objective Redundancy Allocation Problem; T.Sooktip, et al -- A Combined AdaBoost and NEWFM Technique for Medical Data Classification; K.A.Abuhasel, et al -- On sentence length distribution as an authorship attribute; M.Lehtonen -- Learning models for activity recognition in smart homes; L.G.Fahad, et al -- Tackling Class Imbalance Problem in Binary Classification using Augmented Neighborhood Cleaning Algorith.
Keywords: Computational intelligence; Computers; Artificial intelligence; Computational Intelligence; Information Systems and Communication Service; Artificial Intelligence